Classic Hollywood : lifestyles and film styles of American cinema, 1930-1960 - Pravadelli, Veronica, 1964- (University of Illinois Press, 2014)
"Studies of "Classic Hollywood" typically treat Hollywood films released from 1930 to 1960 as a single interpretive mass. Veronica Pravadelli complicates this idea. Focusing on dominant tendencies in box office hits and Oscar-recognized classics, she breaks down the so-called classic period into six distinct phases that follow Hollywood's amazingly diverse offerings from the emancipated females of the "Transition Era" and the traditional men and women of the conservative 1930s that replaced it to the Fifties movie musicals and family melodramas that arose after anti-classic genres like film noir and women's films. Availing herself of the significant advances in film theory and modernity studies that have taken place since similar surveys first saw publication, Pravadelli views Hollywood through strategies as varied as close textural analysis, feminism, psychoanalysis, film style, and study of cinematic imagery, revealing the inconsistencies and antithetical traits lurking beneath Classic Hollywood's supposed transparency. The result is an ambitious, much-needed synthesis of theoretical approaches to a legendary cinematic era."--Publisher's website